An analysis of theta roles of verbs in the Mah Meri language / Maisarah Muhammad Rais - Maisarah, Muhammad Rais (2013)
The Mah Meri language, one of the severely endangered languages of Malaysia is facing the threat of extinction. In order to save valuable information and heritage, this research focusses on the Theta Roles in relation to the verbs in the Mah Meri language. Using Radford’s (1997 & 2009) approach in analysing Theta Roles and the verbs, this study explores the interview data of a Mah Meri native speaker. Two main ideas which are thoroughly examined in this thesis are the Theta Roles and the structural entity of verbs and their related nouns in order to understand the sentential constructions. Thus, in the primary research question, the Theta Roles examined are the Agent, Theme, Experiencer, Benefactor, Instrument, Goal and Locative. These Theta Roles are examined in relation to the verbs found in the data of the study of the Mah Meri language. The second research question addresses the structure of verbs found in the Mah Meri language. In order to fully understand the verb structures, the morphological entities of affixes such as prefixes and suffixes are studied. Moreover, the word order of the sentential constructions are also analysed according to actives and passives. This is done in tandem with analyzing the pronouns in relation to the placement of verbs in a Mah Meri sentential construction. In short, this thesis aims to document the language of Mah Meri in order to preserve the language heritage of Mah Meri.